Pengembangan Sistem Pembelajaran Pemrograman Java yang Atraktif Berbasis Website - Dhanuari Indra Bastari; Fajar Pradana; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Basic programming is a knowledge that must be mastered by every FILKOM student, but based on the result of the questionnaire found that 76% of FILKOM students are more interested in other subject. There are several things that cause students to be less interested in the basic programming courses, the limited source of material that can be obtained and learning techniques that are less varied. Therefore, this research will develop an attractive web-based java learning system by adapting the gamification and IOE-Behavior methods. Gamification method wass applied to this learning system through several features, feature that allows user one challenge other user (challenge), reward feature for user reaching certain condition, level feature and experience point. While the IOE-Behavior method was applied to the java code check feature that allows the system to check the java code automatically by comparing input and output results. This system was developed using SDLC method with waterfall model. In the final stages the system was tested using black-box testing and white-box testing methods with 100% valid test results.